Governmentality in the Context of a Japanese-funded Farm-to- Market Road (FMR) in Agdangan, Quezon Province, Philippines - Teves, Ma. Josephine Therese Emily Galicinao (Studies of Transition States and Societies, 2023)
Recent studies have focused on the role of Official Development Assistance (ODA) in financing infrastructural projects and rural development programmes. This study contributes to this literature by demonstrating how Japanese and Filipino aid authorities facilitate a Japanese-ODA-funded Farm-to-Market Road (FMR) subproject as a solution aiming to achieve overall poverty reduction and rural economic growth in the Philippines. Drawing on Foucault’s governmentality, the paper analyses processes and interactions within the management stages of the FMR subproject. It examines the impact of the completed FMR among agrarian reform beneficiaries (ARBs). It argues that while the FMR fostered mutual understanding and beneficial relationships among aid authorities, more significant advantages were accrued by the non-poor sector. Consequently, ARBs clamour for further support to maximize FMR benefits.